Total Cost of Battery Electric Vehicle (BEV), Hybrid Electric Vehicle (HEV) and Internal Combustion Engine Vehicle (ICEV) in Malaysia - MAIDIN, MUHAMMAD ROSMAIZAM; Norirda Mohamed (Progress in Engineering Application and Technology, 2026)
The increasing adoption of alternative vehicle technologies requires an evaluation of their economic feasibility compared to conventional Internal Combustion Engine Vehicles (ICEVs) in the Malaysian automotive market. This study conducts a total cost of ownership (TCO) analysis of ICEVs, Hybrid Electric Vehicles (HEVs), and Battery Electric Vehicles (BEVs) within the C-segment category. The assessment considers major cost components, including purchase price, maintenance, tyre replacement, energy or fuel consumption, insurance, road tax, and battery replacement where applicable. Cost analysis is performed over a defined ownership period using data obtained from manufacturer specifications, market prices, service schedules, and secondary sources. The results show that ICEVs have lower initial costs but higher long-term operating expenses, while HEVs offer moderate ownership costs. BEVs demonstrate the lowest operating and maintenance costs despite higher initial investment, indicating strong long-term economic potential and supporting sustainable mobility development in Malaysia.